(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The needs of employees in the workplace, including those in healthcare organizations, have been universally regarded as important driver that steer many institutions toward organizational improvement and development. Training needs assessment in the workplace is generally important for any organization as it helps determine gaps, which can manifest in terms of employee knowledge, practice or skill, that are preventing the organization from reaching its desired goals. This study assessed the training needs of barangay service point officers in Baybay City, Leyte, using a descriptive correlational research design. A researcher-made questionnaire was used to obtain the profile and assess the training needs of the 110 research respondents. Majority of the respondents are between the ages of 50 to 59 years old, female, married, high school graduate, have 5 years and above length of service, and have attended training on responsible parenthood and family planning and mothers’ class. Overall, the respondents needed training in terms of knowledge and skills. In terms of the specific training needs, the respondents perceived indicators in knowledge improvement training on various family planning methods, mechanism, effectiveness, and misconceptions; teaching and client education methodologies, and creation and development of effective educational materials as highly needed. For skills improvement training, effective use of communication techniques, effective use of client teaching strategies, and culture competence and sensitivity training were found to be highly needed. In general, there is no significant relationship between the profile of the respondents and their training needs. The current study adds to the understanding of the different training needs of barangay service point officers in terms of their knowledge and skills. The findings offered insights on the importance of continuous capacity-building, which not only addresses current gaps but also prepares BSPOs to adapt to evolving healthcare needs. This initiative advances the goal of providing high-quality, accessible healthcare to all community members, ensuring that services are both responsive and sustainable.